Association of Interleukin-18 Gene Polymorphism with Susceptibility to Visceral Leishmaniasis in Endemic Area of Bihar, an Indian Population - Dinesh Kumar; Puja Tiwary; Jaya Chakravarty; Shyam Sundar (The Scientific World Journal)
Interleukin-18 (IL-18) is a cytokine that mediates Th1 response by inducing interferon-gamma (IFN-γ) production in T cells and natural killer cells. Genetic polymorphisms in the IL-18 gene have been found to be associated with its expression in cancer, tuberculosis, HBV infection, and various other diseases. Lower plasma level of IL-18 in visceral leishmaniasis (VL) patients might be associated with polymorphisms in the regulating or coding region of the gene. Three single nucleotide polymorphisms (SNPs), rs1946519 (−656 G/T) and rs187238 (−137 G/C) in the promoter region and rs549908 (+105 A/C) in the codon region, were genotyped in 204 parasitological confirmed VL patients and 267 controls with no past history of VL. For each locus, polymerase chain reaction (PCR) followed by restriction digestion was performed. IL-18 expression in peripheral blood mononuclear cells (PBMC) collected from VL patients and controls was measured by quantitative real-time RT-PCR. Distribution of G allele at position −656 (P<0.0001) and double haplotypes GGC/GGA (P=0.05) were found to be significantly associated with controls while genotypes TT (P<0.0001) and single haplotypes TGA (P=0.0002), with cases. The inheritance of G allele at the position −656 might be considered as a protective allele for VL.